Analisis Perbandingan Kinerja Keuangan PT. Bank Syariah Mandiri dengan PT. Bank Muamalat Indonesia - Shofia Asry; Wati Rosmawati (STKIP PGRI SITUBONDO, 2022)
This study aimed to investigate and prove empirically about the differences between the financial performance of PT. Syariah Mandiri and PT. Bank Muamalat Indonesia during the period 2017-2021. This study was a descriptive comparative study. The data used are secondary data in the form of financial statements of companies that obtained from published financial statements of Bank Indonesia at www.bi.go.id sites as well as from the official website of each bank. Data analysis was performed using financial ratio analysis of CAR, NPM, ROA, BOPO,LDR. And analysis technique which was use to see the comparison between the performance of Bank Syariah Mandiri and Bank Muamalat Indonesia was the method of Independent sample t-test. The analysis conducted shows that there are significant differences for the ratio of NPM, ROA, BOPO. While the ratio of CAR and LDR there was not a significant difference.